(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study explores the efficacy of stimulation modelling as an innovative pedagogical approach to enhance physics education in Anambra State, Nigeria. Stimulation modelling, involving interactive simulations and conceptual frameworks, aims to bridge conceptual gaps and improve student engagement and understanding. A quasi-experimental design was employed, involving 120 secondary school students across two groups: an experimental group exposed to stimulation modelling and a control group taught via traditional methods. Pre- and post-test assessments measured conceptual understanding and interest in physics. Results indicate significant improvements in the experimental group, suggesting that stimulation modelling could be a viable pathway to revitalize physics education in Anambra State.